1998
DOI: 10.1021/la980394w
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Formation of Hydrophobically Modified Maleic Anhydride and Maleic Acid Copolymers on Various Subphases

Abstract: The formation and transfer of ordered layers of poly(maleic anhydride-alt-alkyl vinyl ether)s and poly(maleic acid-alt-alkyl vinyl ether)s with and without (cyanobiphenylyl)oxy moieties on aqueous subphases is studied by use of the Langmuir−Blodgett technique. The length of the spacers, flexibility of the polyelectrolyte backbone, pH of the subphase, and the presence of counterions determine the orientation of the polymers at the air−water interface. As counterions Cu2+, Mg2+, tetrabutylammonium, n-dodecyltrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The molecular area at the low area side of this plateau, approximately 0.13 nm 2 /repeating unit, is too small to accommodate a monolayer. This indicates that a multilayer is formed upon compression, probably a triple layer (Figure ), as has been observed before for poly(maleic anhydride- alt -vinyl ethers) with cyanobiphenyl mesogens 2 Schematic representation of the transformation of a monolayer into a triple layer. …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The molecular area at the low area side of this plateau, approximately 0.13 nm 2 /repeating unit, is too small to accommodate a monolayer. This indicates that a multilayer is formed upon compression, probably a triple layer (Figure ), as has been observed before for poly(maleic anhydride- alt -vinyl ethers) with cyanobiphenyl mesogens 2 Schematic representation of the transformation of a monolayer into a triple layer. …”
Section: Resultssupporting
confidence: 55%
“…A class of polymers containing maleic anhydride moieties has been applied successfully in LB technology. Although a majority of the studied polymers contains alkyl side chains, , some polymers have been reported that have mesogen-containing side chains. , Recently, novel poly(maleic anhydride- alt -1-alkene)s were synthesized with methoxybiphenyl or cyanobiphenyl mesogens in the side chain . Whereas the polymer with cyanobiphenyl mesogens exhibits a nematic mesophase, the polymers with methoxybiphenyl mesogens exhibit smectic A or higher ordered mesophases .…”
Section: Introductionmentioning
confidence: 99%
“…When the surface pressure drops below the transition pressure, the triple layer ‘unzips’ to regenerate the monolayer. The reproducibility of the isotherms over successive compressions is indicative of a highly flexible system . This behaviour is also attributed to a reorganisation of the chains during the compression process in terms of their degree of hydration and their conformation relative to the conformation observed during spreading.…”
Section: Resultsmentioning
confidence: 87%
“…The reproducibility of the isotherms over successive compressions is indicative of a highly flexible system. 22 This behaviour is also attributed to a reorganisation of the chains during the compression process in terms of their degree of hydration and their conformation relative to the conformation observed during spreading. The same tendency is observed in both copolymers, indicating that the difference in the length of the hydrophilic block is not sufficiently large to affect the stability of the monolayers.…”
Section: Hysteresismentioning
confidence: 99%
“…Electrically conductive films and patterned structures of amphiphilic polythiophenes were formed using LB technique [288]. Amphiphilic diblock copolymers were used for formation and investigation of polymeric Langmuir monolayers and fabrication of organized polymeric films via LB technique [289][290][291][292][293][294][295][296][297][298][299][300][301][302][303]. Surface micelles were observed in a number of diblock copolymer LB films in dependence on polymer composition and monolayer parameters [304][305][306][307][308][309][310][311][312].…”
Section: Organized Planar Polymeric Nanostructuresmentioning
confidence: 99%